Evidence for empagliflozin in heart failure with preserved ejection fraction (HFpEF). Issue 2 (12th December 2022) - Adeyeye, Elizabeth; Khong, Teck K
Abstract: Commentary on: Anker SD, Butler J, Filippatos G, et al . Empagliflozin in heart failure with a preserved ejection fraction. New England Journal of Medicine, 2021; 385:1451–61.